Infliximab clearance decreases in the second and third trimesters of pregnancy in inflammatory bowel disease. Issue 1 (11th February 2021) - Grišić, Ana‐Marija; Dorn‐Rasmussen, Maria; Ungar, Bella; Brynskov, Jørn; Ilvemark, Johan F. K. F.; Bolstad, Nils; Warren, David J.; Ainsworth, Mark A.; Huisinga, Wilhelm; Ben‐Horin, Shomron; Kloft, Charlotte; Steenholdt, Casper
Abstract: Background: Infliximab therapy during pregnancy in inflammatory bowel disease is challenged by a dilemma between maintaining adequate maternal disease control while minimizing fetal infliximab exposure. We investigated the effects of pregnancy on infliximab pharmacokinetics. Methods: The study population comprised 23 retrospectively identified pregnancies. Patients with inflammatory bowel disease were generally in clinical remission at pregnancy conception (74%) and received steady infliximab maintenance therapy (5 mg/kg q8w n = 17; q6w n = 4; q10w n = 1; 10 mg/kg q8w n = 1). Trough blood samples had been obtained in the same patients prior to pregnancy ( n = 119), the first trimester ( n = 16), second trimester ( n = 18), third trimester ( n = 7), and postpregnancy ( n = 12). Data were analyzed using nonlinear mixed‐effects population pharmacokinetic modeling. Results: Dose‐normalized infliximab concentrations were significantly higher during the second trimester (median 15 mg/ml/kg, interquartile range 10–21) compared to prepregnancy (7, 2–12; p = 0.003), the first trimester (9, 1–12; p = 0.04), or postpregnancy (6, interquartile range 3–11; p > 0.05) in patients with inflammatory bowel disease. Similar trends were observed in the third trimester (13, 7–36; p > 0.05). A one‐compartment model with linear elimination described the pharmacokinetics of infliximab (volume of distribution n = 18.2 L; clearance 0.61 L/day). Maternal infliximab exposure was influenced by the second and third trimester of pregnancy and anti‐infliximab antibodies, and not by pregnancy‐imposed physiological changes in, for example, body weight or albumin. Infliximab clearance decreased significantly during the second and third trimesters by up to 15% as compared to pre‐ and postpregnancy and the first trimester. The increased maternal infliximab exposure was weakly associated with lowered clinical disease activity. Pharmacokinetic model simulations of virtual patients indicated the increased maternal infliximab trough concentrations imposed by pregnancy will not completely counteract the decrease in infliximab concentration if therapy is paused in the third trimester. Conclusion: Infliximab clearance decreases significantly in the second and third trimesters, leading to increasing maternal infliximab concentrations in any given regimen. Maternal infliximab levels may thus be maintained as constant in a de‐intensified regimen by therapeutic drug monitoring guidance in inflammatory bowel disease. Key Summary: Summarize the established knowledge on this subject IFX during pregnancy is challenged by a dilemma between maintaining adequate maternal disease control while minimizing fetal drug exposure. Clinicians may refrain from administering IFX in the last part of pregnancy to lower the risk of imposing unknown effects of anti‐TNF‐a therapy on the fetus. International guidelines are conflicting regarding whether IFX should be paused in the third trimester. What are the significant and/or new findings of this study? IFX CL significantly decreases in the second and third trimesters of pregnancy by up to 15%, resulting in increasing maternal circulating IFX levels. Maternal IFX exposure during pregnancy is affected by trimester and anti‐IFX Abs (increasing IFX CL by 69%). Increased maternal IFX exposure during pregnancy correlated weakly with lower disease activity. Maternal IFX concentrations may be maintained at a constant level at a de‐intensified therapeutic regimen in the second and third trimesters via a therapeutic drug monitoring guided‐dose adjustments.